Guidelines for Google Classroom usage as an e-learning tool during Covid-19 pandemic based on similarity search - Lima, Danielli A.; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2022: Anais do XXXIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2022.225329, 2022)
The coronavirus pandemic has changed the routine of almost every school around the world. To solve the problems caused by this disease, many schools adapted and computerized their activities so that the teaching and learning process would not be harmed. Thus, learning management systems were essential, and an example of this type of tool is the Google Classroom, which was widely used in several countries around the world. This article aims to make a similarity search of scientific studies mined by a systematic review to discover guidelines for the implementation of Google Classroom during the pandemic. This study can contribute to the e-learnings implementation not only in the pandemic, but as a support for hybrid and distance classes.